Istri Sebagai Pencari Nafkah dalam Keluarga Perspektif Hukum Islam dan Keadilan Gender - Mardiah, Mardiah (Sharia Journal and Education Center Publishing, 2025)
In Islam, marriage aims to form a harmonious, prosperous, and high-quality family. A family that is of high quality both spiritually and materially. As explained in Marriage Law No. 1 of 1974, the position of the wife as a homemaker means that her economic life must be guaranteed by her husband. This is stated in Article 31 paragraph (3), which states that “The husband is the head of the family and the wife is the homemaker.” Then, Article 34 paragraph (1) states that the husband is obliged to earn money for the sake of the household's economy: “The husband is obliged to provide everything necessary for the household according to his ability.” Meanwhile, Article 34 paragraph (2) regulates the wife's obligation to take care of the household. If the husband or wife neglects their obligations, either party may file a lawsuit under Article 34 paragraph (3). In the Compilation of Islamic Law Article 77 paragraph (2) it is stated that husbands and wives are obliged to love each other, respect each other, be faithful, and provide physical and emotional support to one another. This article automatically closes the door to any attempt at hegemony by either party. This article is sufficient as a basis for the obligations of husbands and wives in fulfilling their obligations and obtaining their respective rights. There is no superiority between the two. All are equal, complementing and perfecting each other. Gender equality is the equal conditions for men and women to obtain their rights as human beings, to play a role and participate in political, economic, socio-cultural, defense and national security activities, and to enjoy the fruits of development equally. Gender construction is considered natural, and as a result, gender influences human beliefs and cultural norms about how men and women should think and act in accordance with these social norms. Eventually, these gender beliefs come to be considered natural, normal, and inherent, so that those who begin to violate them are considered abnormal and unnatural. According to Huzaemah, women are allowed to provide for their husbands, children, and households from the fruits of their labor as long as they are willing to do so. Even if the husband is poor, the wife may give zakat to her husband, but the husband may not give zakat to his wife because she is his responsibility.